2022
DOI: 10.1111/ajt.16743
|View full text |Cite
|
Sign up to set email alerts
|

White paper on antimicrobial stewardship in solid organ transplant recipients

Abstract: Antimicrobial stewardship programs (ASPs) have made immense strides in optimizing antibiotic, antifungal, and antiviral use in clinical settings. However, although ASPs are required institutionally by regulatory agencies in the United States and Canada, they are not mandated for transplant centers or programs specifically. Despite the fact that solid organ transplant recipients in particular are at increased risk of infections from multidrug-resistant organisms, due to host and donor factors and immunosuppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(105 citation statements)
references
References 70 publications
0
105
0
Order By: Relevance
“…18 Unique risk factors in liver transplantation have been suggested Stewardship initiatives in the immunocompromised host are increasing. 19 An area of particular interest is CMV stewardship, given the association of CMV with graft and patient survival. 20 Abbreviations: CMV, cytomegalovirus; D, donor; DBD, donation after brain death; DCD, donation after circulatory death; NASH, nonalcoholic steatohepatitis; PSC, primary sclerosing cholangitis; R, recipient; UC, ulcerative colitis; VL, viral load.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Unique risk factors in liver transplantation have been suggested Stewardship initiatives in the immunocompromised host are increasing. 19 An area of particular interest is CMV stewardship, given the association of CMV with graft and patient survival. 20 Abbreviations: CMV, cytomegalovirus; D, donor; DBD, donation after brain death; DCD, donation after circulatory death; NASH, nonalcoholic steatohepatitis; PSC, primary sclerosing cholangitis; R, recipient; UC, ulcerative colitis; VL, viral load.…”
Section: Discussionmentioning
confidence: 99%
“…Stewardship initiatives in the immunocompromised host are increasing 19 . An area of particular interest is CMV stewardship, given the association of CMV with graft and patient survival 20 .…”
Section: Discussionmentioning
confidence: 99%
“…10 SOT recipients can benefit from traditional AMS activities directed to improve judicious perioperative prescribing and management, but evidence is lacking, although urgently advocated considering the great impact of MDRO in SOT population. 11,12 AMS programs in immunocompetent hosts have shown good results in lowering antimicrobials use, improving patients' outcome, appropriateness and duration of empiric and targeted therapy decreasing CDI rates, shortening length of hospital stay and, as final consequence, reducing health care costs. [13][14][15][16] AMS programs in SOT should also make a step further into personalizing perioperative prophylaxis (PP) and treatments according to the type of transplantation and to the donor-recipient couple, always different and unique.…”
Section: Nonpharmacological Interventions Include Strict Adherence Tomentioning
confidence: 99%
“…Limiting antimicrobial duration may mitigate detrimental effects of antibiotics and are a potential target for antimicrobial stewardship intervention. 3 In the last two decades, a number of studies have demonstrated the efficacy of shorter courses of antibiotics for a variety of clinical syndromes. [4][5][6][7] However, most of the studies conducted to date either explicitly excluded immunocompromised patients (including SOTRs) [8][9][10][11][12][13][14][15][16][17][18][19] did not report whether immunocompromised subjects were enrolled, [20][21][22][23][24][25][26][27][28][29][30] or recruited too few patients to draw conclusions about antibiotic duration in this subset.…”
Section: Introductionmentioning
confidence: 99%